2018
DOI: 10.21873/anticanres.13133
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Sarcopenia and Systemic Inflammatory Response in Patients With Esophageal Cancer

Abstract: Background/Aim: The association between the presence of sarcopenia and systemic inflammatory response is unclear in patients with esophageal cancer. This study was performed to investigate the relationship between sarcopenia and systemic inflammatory response and clarify the effect of these factors on the prognosis in patients with esophageal cancer. Patients and Methods: This study included 163 patients with esophageal cancer. The patients' body composition was assessed before esophagectomy using multifrequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…For articles that remained after the initial screen, 65 full texts were reviewed for eligibility. Ultimately, 24 studies were selected for inclusion in the systematic review-18 articles [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]47] and 6 abstracts [33, 44-46, 48, 53]-with a total of 3,607 patients. Table 2 provides an overview of included studies regarding number of study participants, cancer types, inclusion criteria, and stage of care when the BIA assessment was conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For articles that remained after the initial screen, 65 full texts were reviewed for eligibility. Ultimately, 24 studies were selected for inclusion in the systematic review-18 articles [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]47] and 6 abstracts [33, 44-46, 48, 53]-with a total of 3,607 patients. Table 2 provides an overview of included studies regarding number of study participants, cancer types, inclusion criteria, and stage of care when the BIA assessment was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, BIA-defined sarcopenia was associated with adverse clinical outcomes in adults with cancer [29,30,32,34,36,37,39,45,47,48,51,53]. Sarcopenia was associated with worse overall survival in five studies [27,34,42,48,51] and severe surgical complications (e.g., infection, hematological) in four studies [30,32,37,47]. Other outcomes included worse pathological response in patients with esophageal cancer treated with chemotherapy [36], worse inflammatory response in patients with esophageal cancer treated with surgery [34] (which may preclude worse surgical response, e.g., more infections, higher reoperation rates), and higher patient-reported pain, fatigue, insomnia, and constipation [42].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the effect of sarcopenia on the prognosis of esophageal cancer. However, the results were contradictory [17,18,[20][21][22][23]. In addition, only a few studies included patients who received NACRT instead of chemotherapy as a NAT, and none of these studies demonstrated a significant relationship between sarcopenia and OS [17,23].…”
Section: Discussionmentioning
confidence: 99%
“…While several studies showed that sarcopenia is a risk factor for poor survival [20][21][22], some others did not [17,18,23]. Furthermore, because most patients included in these studies received chemotherapy rather than chemoradiotherapy as a neoadjuvant treatment (NAT) [18,[20][21][22], changes in skeletal muscle mass and laboratory test results before and after NACRT have not been well-studied. Therefore, this study aimed to assess whether sarcopenia and loss of skeletal muscle affected survival outcomes of esophageal cancer patients who received NACRT followed by surgery.…”
Section: Introductionmentioning
confidence: 99%
“…And inflammatory response is one of the main manifestations of postoperative. Changes in serum inflammatory cytokines can objectively reflect the state of postoperative inflammatory response of patients [27].…”
Section: Discussionmentioning
confidence: 99%